ZEN AND HEALING - Ichiro, Okumura (Journal of Dharma, 1999)
On being asked to write something on the theme "Zen and Healing" my first reaction, I must admit, was bewilderment: the Zen I have been familiar with till now has never dealt with the problem of healing in the commonly accepted meaning of the word. Then suddenly I remembered the advice of Ryokan (1758-1831), the Zen monk, who has been called the St. Francis of the East: "When you meet misfortune hail it; when' death comes welcome it; that is the best way to avoid disaster.